An Overview of Indian Dacine Fruit Flies (Diptera: Tephritidae: Dacinae: Dacini) - Vasudha, A.; Ahmad, Md. Abbas; Agarwal, M. L. (International Journal of Bio-resource and Stress Management, 2019)
Fruit flies belonging to tribe Dacini are pertinent pests of horticultural crops in Southeast Asia, Sub-Saharan Africa and Australasian Oceanian region. They pose enormous threats to fruit and vegetable production throughout the world, causing both quantitative and qualitative losses. Ninety two species of dacine fruit flies (28 endemic, 30.43% endemism) belonging to three genera, viz. Bactrocera Macquart (51 species, 17 endemic, 33.33% endemism), Dacus Fabricius (10 species, 3 endemic, 30.0% endemism), and Zeugodacus Hendel (31 species, 8 endemic, 25.80% endemism), and 19 subgenera have been listed from India. Of these, nine endemic species, viz. Bactrocera (Bactrocera) andamanensis, B. (B.) blairiae, B. (B.) curtivitta, B. (B.) patula, B. (B.) ranganathi, B. (Calodacus) harrietensis, Dacus (Mellesis) insulosus, Zeugodacus (Zeugodacus) fuscoalatus, Z. (Z.) havelockiae are known only from Andaman & Nicobar Islands. The current understanding of the morphology of the tribe, together with data on their biology, habitat associations, and distribution combine presents a picture of the phylogenetic relationships within the group. Besides, the knowledge of biology and behaviour of dacine species suggests that there is a close relationship between the fly species and their host plants which involves adult’s feeding, host recognition, courtship and mating, oviposition, larval feeding and bacteria associations. In the present paper notes on subgeneric classification of Dacini, their distribution, endemism, relative occurrence of different taxa, phylogeny, host associations, pest status, male lures and bacterial associations have been added.